Preliminary study on the adsorption of lead (II) ions from aqueous solution with breadfruid’s bark (Artocarpus altilis) by un-modified and modified with citric acid - Lia Mairiza; Muhammad Zaki; . Nurhayati; Evi Juliyanti (Syiah Kuala University, 2011)
The adsorption of lead(II) ions from aqueous solution with breadfruit’s bark by unmodified and modified with citric acid was investigated. The results by using adsorbent dosage 20 g/L indicated the adsorption efficiency was up to 99%, and the best result is obtained about 99,963% when adsorbate is conducted with modified bark for 90 minutes. The adsorption behavior by modified bark followed the Langmuir isotherm model and the Freundlich isotherm model for modified bark. The maximum adsorption capacity of lead(II) ions are 34,98 mg adsorbate/g adsorbent for unmodified bark when contact time is 60 minutes. The influence of contact time showed that adsorption reached the equilibrium rapidly. A batch adsorption model followed the pseudo second order kinetic.